MoyaMoya Disease in a Child: a Case Report - Joarder, MA; Chandy, M (Pulse, 2014)
Acute stroke is an infrequent disease of pediatric age group patients. MoyaMoya is a rare cerebro vascular disease of unknown etiology. We report a case of 14-year-old male child who presented with right-sided hemiplegia and diagnosed as a MoyaMoya disease. MoyaMoya disease is rare, but important as a cause of cerebral stroke in children. Cerebral revascularization surgery leads to favorable outcome. DOI: http://dx.doi.org/10.3329/pulse.v6i1-2.20357 Pulse Vol.6 January-December 2013 p.62-65